Utilization of Multimedia Facilities in the Teaching of Biology among Secondary Schools Students in Obudu Local Government Area of Cross River State - Stella Ekwutosi Nkwocha (Journal of Digital Learning and Education, 2023)
This study was designed to ascertain the extent of utilization of multimedia facilities among Secondary School Students in Obudu Local Government Area of Cross River State. The study adopted the quasi experimental design, specifically the pretest posttest non-equivalent group design.  Two research questions and hypotheses were formulated, answered and tested respectively. The population consists of 527 senior secondary school students. The sample was made up of two hundred and fifty students (one hundred and thirty males and one hundred and twenty females). The data were collected using Questionnaire titled” Multimedia Facilities in Biology questionnaire (MFBQ)” and “Biology Achievement Test (BAT)”. The instruments were validated by experts. Data were analyzed using percentage and mean for research questions with a bench mark of 2.5 while chi –square and T-tests were used to test the hypotheses at p<0.05 significance. The result from the findings revealed that the students taught using multimedia facilities performed better than those not taught with multimedia facilities, multimedia facilities were not available enough in the secondary schools in Obudu, teachers’ competence in the use of multimedia facilities was good as observed from the frequency of use which had influence on students’ academic achievement in Secondary Schools Obudu Local Government of Cross River State. It was however inferred based on the findings that the failure rate of students will be reduced if appropriate and relevant multimedia facilities were provided for the teaching of biology in secondary schools. Finally, it was recommended among others that the teaching of biology in secondary schools in Obudu should be conducted in the manner that students will effectively understand and learn the concepts taught with the use of the multimedia facilities and that the Federal and State Government should periodically organize and sponsor teachers’ attendance to conferences, seminars and workshops on utilization of multimedia facilities in teaching and learning processes.